2009
DOI: 10.2114/jpa2.28.15
|View full text |Cite
|
Sign up to set email alerts
|

Perception of spatial requirements for wheelchair locomotion in experienced users with Tetraplegia

Abstract: This study focused on whether wheelchair users showed enhanced ability to estimate the space required for locomotion with familiar and unfamiliar wheelchairs. Tetraplegic participants, who lacked somatosensory input from the upper limbs and were unable to obtain information about the dimensions of a wheelchair from their hands, and ablebodied control participants made judgments of whether a doorway was passable with their usual form of locomotion (use of a familiar wheelchair or walking) or a new form of locom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…This assistive device offers the possibility, at least in principle, to partially “repair” the motor functionality of the damaged body part [24], [41] and appears conceived not as an object to move but as a mediator of the limbs’ action. This reorganization of body model is consistent with the positive inclusion of the wheelchair to accommodate physical impairment and restore mobility [13][15], [18], [42], [43]. The perceived bodily experience is that of being functionally whole, and the system reorganizes itself to achieve its original balance, which enables the immobile user to act in the world.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This assistive device offers the possibility, at least in principle, to partially “repair” the motor functionality of the damaged body part [24], [41] and appears conceived not as an object to move but as a mediator of the limbs’ action. This reorganization of body model is consistent with the positive inclusion of the wheelchair to accommodate physical impairment and restore mobility [13][15], [18], [42], [43]. The perceived bodily experience is that of being functionally whole, and the system reorganizes itself to achieve its original balance, which enables the immobile user to act in the world.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, we aimed to establish the effect of sensorimotor loss, and the specific use of this tool, on wheelchair embodiment. It is important to note that previous SCI studies have already demonstrated the physical adjustment to, [7], [15], [16], [18] and brain representation of [17], the “body plus wheelchair” being perceived as one. We also capitalized on the fact that 12 of the patients recruited for this study were tested in a separate experiment that indicated patients with SCI embody functionally relevant wheelchair action sounds (unpublished data, presented in Galli et al, Concepts, Actions, and Objects; Functional and Neural Prospective Meeting Abstract, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…One key finding supporting this understanding was that the critical ratio value for beginning rotation was constant among individuals regardless of the individual’s body size [1]. This was a case even when horizontal space required for passage is transiently wider than the body because a participant was transporting an external object [2], [3], [4], [5], [6], although this seems to occur only for well learned behavior [7].…”
Section: Introductionmentioning
confidence: 91%
“…In some ways, individuals in absence of sensory motor signals from peripheral body parts may also paradoxically be more sensitive to visual body configurations and possible distortions per se. In this regard, the subjective broadening of the shoulders in insentient and immobile patients with an SCI is interesting and reflects the referencing of body width to the width of a wheelchair [2527], suggesting that the absence of normal body sensations may play a larger role in the perceptual recalibration of the body [28, 29]. When using salient body-assistive tools, the persistent visual motor exposure to an assistive device becomes an important mediator of implicit corporeal knowledge.…”
Section: Visual Input In the Construction Of Body Distortionsmentioning
confidence: 99%